The multilevel p2 model: A random effects model for the analysis of multiple social networks - Zijlstra, B; van Duijn, MAJ; Snijders, T (2006)
The p2 model is a random effects model with covariates for the analysis of binary directed social network data coming from a single observation of a social network. Here, a multilevel variant of the p2 model is proposed for the case of multiple observations of social networks, for example, in a sample of schools. The multilevel p2 model defines an identical p2 model for each independent observation of the social network, where parameters are allowed to vary across the multiple networks. The multilevel p2 model is estimated with a Bayesian Markov Chain Monte Carlo (MCMC) algorithm that was implemented in free software for the statistical analysis of complete social network data, called StOCNET. The new model is illustrated with a study on the received practical support by Dutch high school pupils of different ethnic backgrounds. © 2006 Hogrefe and Huber Publishers.